Integration of phase change materials in improving the performance of heating, cooling, and clean energy storage systems: An overview. (1st September 2022) - Ahmed, Shams Forruque; Rafa, Nazifa; Mehnaz, Tabassum; Ahmed, Bushra; Islam, Nafisa; Mofijur, M.; Hoang, Anh Tuan; Shafiullah, G.M.
Abstract: Phase change materials (PCMs) have garnered significant attention as low-cost thermal energy storage systems that efficiently capture and store solar energy. Recent review works have largely focused only on thermal conductivity enhancement techniques, and/or applications of PCMs, while others have mainly discussed the performance enhancement of either heating, cooling, or clean energy storage systems integrating with PCMs. However, not enough studies recently reviewed all of these techniques/systems comprehensively to provide insights into them. This paper thus comprehensively reviews the integration of PCMs as an enhancement to most types of heating, cooling, and clean energy storage system performance, and the techniques to enhance thermal conductivity. The integration of PCMs with these systems has shown promising performance. For instance, an improvement of 13.5% is found in the efficiency of photovoltaic (PV) system when it is integrated with PCM/Al2 O3 nanoparticles. In addition, the solar air heater's daily energy efficiency reaches 17% on its own, but when combined with PCM, it reaches 33%. However, the major drawback of using PCM–TES (thermal energy storage) for cooling is that PCM does not entirely solidify at night. The literature also shows that the issues related to PCMs' low thermal conductivity, phase separation, and subcooling/supercooling, their poor compatibility with other materials, and the environmental hazards they pose hinder their application on a large scale. It is necessary to implement international standards for assessing the thermophysical properties of PCMs and compile data to better facilitate the utilization of PCMs by end-users.